Implementing Pancasila Values in the Era of Globalization - Dewi, Gina Dewi Sabrina; Nairiza syifa, Ningrum; Fathur Rahman, Adi Negara; Rara Fitra, Ramadani; Sabrina, Sabrina; Anisah , Apriliani; Anita Zahra, Amelia (Jurnal Edukasi Terkini, 2025)
Purpose- In the era of globalization, the application of Pancasila values in social, national, and state life faces increasing challenges. The mindset, behavior, and national identity of the Indonesian people are influenced by globalization, driven by technological advancements, more open global interactions, and socio-cultural changes. This study aims to explore how Pancasila values are applied in the modern world amidst these globalizing forces. Research Methodology / Design / Approach-This study employs a qualitative approach to analyze the relevance and application of Pancasila values in contemporary Indonesian society. It examines the impact of globalization on national identity and cultural values, focusing on how these influences affect the internalization and practice of Pancasila principles. Finding-The study finds that Pancasila remains the foundational ideology of the nation. However, its application in daily life is often hindered by the negative effects of globalization, such as rising individualism, materialism, and the erosion of local cultural values. These challenges necessitate deliberate efforts to enhance the understanding and internalization of Pancasila through education, public policy, and active community engagement. Originality/Value- This research highlights the enduring relevance of Pancasila as a moral foundation in facing contemporary global challenges. It emphasizes the need for planned and sustained actions to preserve and strengthen Pancasila values, ensuring they continue to guide Indonesia’s social and national life in a rapidly changing world.